Meta-analysis of the effect of bariatric surgery on physical function. Issue 9 (12th June 2018) - Adil, M T; Jain, V; Rashid, F; Al-taan, O; Whitelaw, D; Jambulingam, P
Abstract: Background: Obesity leads to an impairment of physical function that limits the ability to perform basic physical activities affecting quality of life. Literature on the effect of bariatric surgery on physical function is confounding and generally of low quality. Methods: A comprehensive search was undertaken using MEDLINE, Scopus (including Embase), CENTRAL, PubMed, SPORTDiscus, Scirus and OpenGrey for published research and non-published studies to 31 March 2017. Studies employing objective measurement and self-reporting of physical function before and after bariatric surgery were included. The magnitude of experimental effect was calculated in terms of the standardized mean difference (MD), and confidence intervals were set at 95 per cent to reflect a significance level of 0·05. Results: Thirty studies including 1779 patients met the inclusion criteria. Physical function improved after bariatric surgery at 0–6 months (MD 0·90, 95 per cent c.i. 0·60 to 1·21; P < 0·001), more than 6 to 12 months (MD 1·06, 0·76 to 1·35; P < 0·001) and more than 12 to 36 months (MD 1·30, 1·07 to 1·52; P < 0·001). Objective assessment of physical function after bariatric surgery showed improvement at 0–6 months (MD 0·94, 0·57 to 1·32; P < 0·001), more than 6 to 12 months (MD 0·77, 0·15 to 1·40; P = 0·02) and more than 12 to 36 months (MD 1·04, 0·40 to 1·68; P = 0·001). Self-reported assessment of physical function showed similar improvements at 0–6 months (MD 0·80, 0·12 to 1·47; P = 0·02), more than 6 to 12 months (MD 1·42, 1·23 to 1·60; P < 0·001) and more than 12 to 36 months (MD 1·41, 1·20 to 1·61; P < 0·001) after a bariatric procedure. Conclusion: Bariatric surgery improves physical function significantly within 6 months of the procedure and this effect persists over time to 36 months after surgery, whether measured objectively or by self-reporting. Abstract : Improves physical function